PERANAN GURU DALAM MENGENALKAN SHALAT DI TK AISYIYAH BUSTANUL ATHFAL 2 PONTIANAK - Marni Juliarty Evy Ernie; Muhamad Ali; Dian Miranda (Universitas Tanjungpura, 2019)
AbstractThis research is motivated by the efforts made by the teacher in introducing prayer to children of kindergarten. Prayers that are applied include sunnah prayer and obligatory prayer, but in this case the main focus that the teacher introduces to the child is obligatory prayer which is the duty of all Muslims in the world to worship. The research method that will be used in this research is descriptive research with a qualitative approach. The research subjects were 1 teacher and 20 children. Based on the results of the study in general, a conclusion can be drawn that: 1) The role of the teacher in introducing the prayer readings performed by the teacher by determining specific instructional objectives and determining the implementation of work by the teacher. Thus the teacher is more focused on the implementation of learning. 2) The role of the teacher in introducing the prayer movements performed by the teacher by preparing learning preparation activities, presenting learning methods, concluding activities. 3) The role of the teacher in introducing prayer prayer is done by the teacher with more focus on the purpose of the learning method to introduce prayer to children. Based on the findings made during the research period, it can be suggested to the teacher in learning activities that is so that the teacher can plan learning media that interest the child. Keywords: the role of the teacher, introduce prayer